2006
DOI: 10.1111/j.1539-6924.2006.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Containment of Polioviruses After Eradication and OPV Cessation: Characterizing Risks to Improve Management

Abstract: The goal of the World Health Organization is to stop routine use of oral poliovirus vaccine shortly after interruption of wild poliovirus transmission. A key component of this goal is to minimize the risk of reintroduction by destruction of polioviruses except in an absolute minimum number of facilities that serve essential functions and implement effective containment. Effective containment begins with a complete facility risk assessment. This article focuses on characterizing the risks of exposure to poliovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 185 publications
(292 reference statements)
1
45
0
Order By: Relevance
“…This is considered to have a role in virus transmission between close contacts but is not likely to contribute strongly to the load of virus in the environment. The amount of virus excreted into stools is known to be variable with maximal amounts reaching 10 7 infectious doses/day per person [10]. PVs are relatively stable in aqueous environments at ambient temperatures and adsorption to various solid materials in the environment may further extend the time over which at least part of the infectivity can be recovered.…”
Section: Rationale Of Env Is Based On the Natural Course Of Pv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is considered to have a role in virus transmission between close contacts but is not likely to contribute strongly to the load of virus in the environment. The amount of virus excreted into stools is known to be variable with maximal amounts reaching 10 7 infectious doses/day per person [10]. PVs are relatively stable in aqueous environments at ambient temperatures and adsorption to various solid materials in the environment may further extend the time over which at least part of the infectivity can be recovered.…”
Section: Rationale Of Env Is Based On the Natural Course Of Pv Infectionmentioning
confidence: 99%
“…Environmental contamination with faecal effluents, increasing use of wastewater in agriculture, and declining PV population immunity are all likely future risk factors for ingestion and transmission of PVs [10]. ENV can be an important tool for shortening the response time between awareness of a PV reemergence event and response.…”
Section: Concluding Remarks and Future Viewsmentioning
confidence: 99%
“…The risks of poliovirus releases or other laboratories highlight the need to focus additional efforts on containment now that the post-OPV era is well underway for serotype 2 [4,38,39,62,63]. In this respect, work to develop IPV seed strains that do not replicate or revert to a neurovirulent and transmissible form offers the potential for safer IPV production in otherwise high-risk countries.…”
Section: Factors Affecting Current Opv Restart Riskmentioning
confidence: 99%
“…Secondary treatments that incorporate a filtration step (i.e., tertiary treatment) remove more fine particles that in turn reduces effluent virus content by 1 to 2.4log 10 (Dowdle et al, 2006). A cautionary note: low levels of enteroviruses detected in influent in many studies may result in an overestimation of the efficiency of secondary treatment (Qiu et al, 2015).…”
Section: Secondary Treatmentmentioning
confidence: 99%
“…Poliovirus can survive for at least 12 days in soils at 37°C and for months at temperatures at or below 4°C when moisture content is above 2.9%, but are rapidly eliminated within a few days when moisture content is ≤1.2% (Dowdle et al, 2006). Sensitivities may vary among different isolates of the same virus serotype (for example see Dowdle et al (2006) for differences between oral poliovirus strains and wild polioviruses). Studies have shown that the extent of virus adsorption differ among the soil types and among the viruses.…”
Section: Persistence In Biofilmsmentioning
confidence: 99%